IMPLEMENTASI MEDIA PEMBELAJARAN KARTU MAKE A MATCH PADA MATA PELAJARAN PPKN KELAS III DI SDS AL FATH BSD UNTUK MENINGKATKAN HASIL BELAJAR (Adi Widya: Jurnal Pendidikan Dasar, 2023)
Learning is an activity undertaken by students to acquire knowledge for future use. However, at present, many learning models have caused students to become less enthusiastic about participating in them. The observed fact is that there are still many students in class 3-D at SDS Al Fath BSD who receive grades below the Minimum Competency Criteria (KKM). This is primarily due to the use of traditional teaching models, which consequently affect the learning objectives. One of the interactive learning models is 'Make a Match.' This study aims to determine the impact of using the 'Make a Match' card media on the learning outcomes of PPKn (Civics and Citizenship Education) students regarding the diversity of regional specialties in Indonesia, specifically in the third-grade class at Elementary School (SD) 3-D. This research falls under the category of Classroom Action Research (CAR). The research subjects consist of 22 students participating in the SD 3-D class. The study employs three cycles: pre-cycle, cycle 1, and cycle 2. In the pre-cycle, it was found that the completion rate was 31.82%, which is below the Minimum Competency Criteria (KKM) threshold of 70%. In cycle 1, the completion rate rose to 81.82%, indicating that learning outcomes exceeded the KKM of 70%. In the second phase, the graduation rate reached 90.91%, once again surpassing the KKM. Based on the results of this study, it can be concluded that the development of student learning outcomes is influenced by the teaching model and the instructional media used. 'Make a Match' learning fosters student activity, creativity, and motivation throughout the learning process